A novel mutant Na+/HCO3− cotransporter NBCe1 in a case of compound‐heterozygous inheritance of proximal renal tubular acidosis. (2nd August 2016) - Myers, Evan J.; Yuan, Lu; Felmlee, Melanie A.; Lin, Yuan‐Yuan; Jiang, Yan; Pei, Yu; Wang, Ou; Li, Mei; Xing, Xiao‐Ping; Marshall, Aniko; Xia, Wei‐Bo; Parker, Mark D.
Abstract : Key points: The inheritance of two defective alleles of SLC4A4, the gene that encodes the widely‐expressed electrogenic sodium bicarbonate cotransporter NBCe1, results in the bicarbonate‐wasting disease proximal renal tubular acidosis (pRTA). In the present study, we report the first case of compound‐heterozygous inheritance of pRTA (p.Arg510His/p.Gln913Arg) in an individual with low blood pH, blindness and neurological signs that resemble transient ischaemic attacks. We employ fluorescence microscopy on non‐polarized (human embryonic kidney) and polarized (Madin–Darby canine kidney) renal cell lines and electrophysiology on Xenopus oocytes to characterize the mutant transporters (R510H and Q913R). Both mutant transporters exhibit enhanced intracellular retention in renal cells, an observation that probably explains the HCO3 − transport deficit in the individual. Both mutants retain a close‐to‐normal per molecule Na + /HCO3 − cotransport activity in Xenopus oocytes, suggesting that they are suitable candidates for folding‐correction therapy. However, Q913R expression is uniquely associated with a depolarizing, HCO3 − independent, Cl − ‐conductance in oocytes that could have pathological consequences if expressed in the cells of patients. Abstract: Proximal renal tubular acidosis (pRTA) is a rare, recessively‐inherited disease characterized by abnormally acidic blood, blindness, as well as below average height and weight. pRTA is typically associated with homozygous mutation of the solute carrier 4 family gene SLC4A4 . SLC4A4 encodes the electrogenic sodium bicarbonate cotransporter NBCe1, a membrane protein that acts to maintain intracellular and plasma pH. We present the first description of a case of compound‐heterozygous inheritance of pRTA. The individual has inherited two mutations in NBCe1: p.Arg510His (R510H) and p.Gln913Arg (Q913R), one from each parent. In addition to the usual features of pRTA, the patient exhibits unusual signs, such as muscle spasms and fever. We have recreated these mutant transporters for expression in model systems. We find that both of the mutant proteins exhibit substantial intracellular retention when expressed in mammalian renal cell lines. When expressed in Xenopus oocytes, we find that the R510H and Q913R‐mutant NBCe1 molecules exhibit apparently normal Na + /HCO3 − cotransport activity but that Q913R is associated with an unusual HCO3 − independent anion‐leak. We conclude that a reduced accumulation of NBCe1 protein in the basolateral membrane of proximal‐tubule epithelia is the most probable cause of pRTA in this case. We further note that the Q913R‐associated anion‐leak could itself be pathogenic if expressed in the plasma membrane of mammalian cells, compromising the benefit of strategies aiming to enhance mutant NBCe1 accumulation in the plasma membrane. Key points: The inheritance of two defective alleles of SLC4A4, the gene that encodes the widely‐expressed electrogenic sodium bicarbonate cotransporter NBCe1, results in the bicarbonate‐wasting disease proximal renal tubular acidosis (pRTA). In the present study, we report the first case of compound‐heterozygous inheritance of pRTA (p.Arg510His/p.Gln913Arg) in an individual with low blood pH, blindness and neurological signs that resemble transient ischaemic attacks. We employ fluorescence microscopy on non‐polarized (human embryonic kidney) and polarized (Madin–Darby canine kidney) renal cell lines and electrophysiology on Xenopus oocytes to characterize the mutant transporters (R510H and Q913R). Both mutant transporters exhibit enhanced intracellular retention in renal cells, an observation that probably explains the HCO3 − transport deficit in the individual. Both mutants retain a close‐to‐normal per molecule Na + /HCO3 − cotransport activity in Xenopus oocytes, suggesting that they are suitable candidates for folding‐correction therapy. However, Q913R expression is uniquely associated with a depolarizing, HCO3 − independent, Cl − ‐conductance in oocytes that could have pathological consequences if expressed in the cells of patients.